TUGAS DAN WEWENANG BADAN ANGGARAN DPRD KOTA BEKASI DALAM PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) - William Franata, Retno Saraswati,Henny Juliani (Diponegoro Law Journal, 2012)
Budget Function of  The Regional Parliaments of of the Council in addition to the focused on the function of Regional Expenditure. In performing these functions conducting the discussion. Approved Regional Parliament itself. Budget Board City fittings that are fixed and the No. 27 of 2009 on the MPR, DPRto the Legislation and Oversight functions. Budget Function Regional Parliament in the preparation of the Budget these functions Regional Parliament to cooperate with the mayor Approved or not a draft budget in the future is a decision Budget Board or called Banggar is Regional Parliament of Bekasi and the budget is devoted to a discussion. Contained in DPR, DPD and DPRD.Issues raised in the writing of Council Bekasi in the discussion experienced Budget Board of Regional Parliament budget.in the writing of this law is how the duties and authority of in the discussion and approval of budgets and what barriersBudget Board of Regional Parliament Bekasi City in the discussionThe method used in this study is used in this study is deskiptif-analytical, the theories of jurisprudence. In this study role on the things that are not written, Volume 1, Nomor 4, Tahun 2012 TUGAS DAN WEWENANG BADAN ANGGARAN DPRD KOTA BEKASI DALAM PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD)Fakultas Hukum, Universitas Diponegoro 76918201 Fax : 024-76918206in this study is the approach that is empirical juridical analytical, as this study illustrates the applicable In this study, the data provided by informants play an important written.Duties and powers of Regional Parliament Of Bekasi City Regional Parliament  Regulation Bekasi City. Budget Board itself was Budget Board became involved Priorities and Budget Ceiling While frequent meetings with Working each SKPD. Barriers faced in conducting external parties, from the Working Units Units bargaining must take placeof the three functions Budget Function more the Budget Revenue and with the mayor in is a decision of theRegional Parliament of Bekasi Contained in the Budget Actauthority of the Budget barriers or constraints in the discussion and approval ofempirical juridical. Specification the applicable laws relating toplay an important Regional Parliament Of Bekasi City Budget Board Regulation No. 1 of 2010 on the order of The Regional Parliaments of Budget Board itself is set in The Regional Parliaments of itself was not involved from the beginning in the budget process since the establishment of Public Policy Budgetin the budget process. Budget (KUA) and theBudget Ceiling While (PPAS). In a discussion the budget, the Budget Agency Working Units (SKPD) in the target revenue (PAD) to be achievedthe Budget Agency to be achieved by actually comes from from each Working e Working Units. in conducting discussions Budget Board budget actually comes Working Units. In determining the revenue targets fromtake place between the Regional Parliament and the Working Units.Working Units with all its problems expected target of Regional Parliament all its problems in the field, of course, will not immediately Parliament.